Plan indicativo de mediano plazo: el IICA en los próximos cinco años - Instituto Interamericano de Ciencias Agrícolas (IICA) (Instituto Interamericano de Ciencias Agrícolas (IICA), 2021)
The objectives of the plan are to continue, in a systematic way, the operationalization of the General Plan; offer better elements of judgment to the IICA authorities and its technical staff for decision-making and for planning and executing the Institute's technical cooperation actions; provide the countries with specific information on the doctrine of IICA and the specific possibilities of action of the Institute.